The mediating role of digital health literacy in the relationship between social support and health-promoting lifestyle among occupational populations: a cross-sectional study - Yun Pan; Tantan Cheng; Tianyu Sha; Jiakui Zhao; Yeqing Gu (Frontiers in Public Health, 2026)
Background In the digital age, health-promoting lifestyle (HPL) among occupational populations is critical for chronic disease prevention. Social support has been recognized as a key facilitator of HPL, yet the underlying mechanisms remain unclear. Digital health literacy (DHL)—the ability to access, understand, and apply online health information—may serve as a potential mediator. However, empirical evidence on this mediation model in occupational settings is limited. This study aims to examine the mediating role of DHL in the relationship between social support and HPL among occupational populations. Methods A multistage stratified cluster sampling method was used to recruit 1,030 occupational participants in Huangpu District, Shanghai, between July and September 2024. Data were collected using standardized questionnaires assessing social support, DHL, and HPL. Descriptive statistics, Pearson correlation analysis, and bootstrap-based mediation analyses were conducted. Results Social support was positively correlated with DHL ( r = 0.176, P < 0.001) and HPL ( r = 0.324, P < 0.001), while DHL was also positively associated with HPL ( r = 0.306, P < 0.001). Mediation analysis indicated that DHL partially mediated the relationship between social support and HPL (indirect effect = 0.113, 95% CI [0.065, 0.170]), accounting for 13.9% of the total effect. Parallel mediation analysis further showed that only the application dimension of DHL had a significant mediating effect (effect = 0.081, 95% CI [0.026, 0.146]), whereas the other dimensions were not significant. Conclusions Social support is positively associated with HPL both directly and indirectly through DHL. Notably, the application of digital health information plays a key role in translating social support into health-promoting behaviors. Interventions aiming to improve occupational health should prioritize not only strengthening social support but also enhancing individuals' ability to apply digital health information in daily life.